Imaging in Sports-Specific Musculoskeletal Injuries - Guermazi, Ali; Roemer, Frank W.; Crema, Michel D. (Springer International Publishing : Imprint: Springer, 2016)
Most books on imaging in sports medicine are concerned with the particular joints or anatomy involved in sports-related injuries. This book, however, takes a different perspective by looking at injuries that are associated with specific sports. All of the well-known major sports, such as football, tennis, and basketball, are included, as are many less common but still very popular sports, such as baseball, American football, and rugby. Because the popularity of different sports varies widely from country to country and region to region, this book should be especially useful to radiologists and physicians who are looking for information on injuries related to the sports that are popular where they practice or with which they are not familiar. Imaging plays an important role in every aspect of sport injuries: at diagnosis, follow-up, and return to action. It also plays a role in injury classification and hence helps to predict the time required for full recovery. The chapters on sports-specific injuries are preceded by two chapters on the perspective of clinicians and another two chapters on the general use of MR imaging and ultrasound in sports medicine. The authors of the book are world-renowned experts from five continents. Imaging in Sports-Specific Musculoskeletal Injuries should be of great interest to radiologists, sports medicine physicians, orthopedic surgeons, and rehabilitation physicians, and to anyone interested in the treatment of sports-related in juries.